Effect of airway pressure on lumbar epidural pressure during positive pressure ventilation - Sun Sook Han; Young Jin Lim; Yunseok Jeon; Kyoung-Beom Min; Won-sik Ahn; Sang Chul Lee (Korean Journal of Anesthesiology, 2011)
BackgroundThe purpose of this study was to measure lumbar epidural pressure (EP) during the insertion of a Tuohy needle under general anesthesia and to evaluate the influence of airway pressure on EP.MethodsLumbar EP was measured directly through a Tuohy needle during intermittent positive pressure ventilation in fifteen patients. Mean and peak EP were recorded after peak inspiratory pressures (PIP) of 0, 15, and 25 cmH2O.ResultsAll measured lumbar EPs were positive, with the pressure increasing during inspiration and decreasing during expiration. Median EP was 6.0 mmHg (interquartile range, 4.0-8.0) at 0 cmH2O of PIP, 6.5 mmHg (4.5-8.5) at 15 cmH2O, and 8.5 mmHg (6.0-10.5) at 25 cmH2O, increasing significantly at 15 cm H2O PIP, and further increasing at 25 cmH2O (P < 0.001).ConclusionsWe demonstrate the influence of increased airway pressure on lumbar EP measured directly through a Tuohy needle. Lumbar EPs were positive, and increasing PIP levels significantly increased lumbar EP.